2017
DOI: 10.1016/j.msea.2017.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of polycrystal plasticity to slip system kinematic hardening laws for Al 7075-T6

Abstract: The prediction of formation and early growth of microstructurally small fatigue cracks requires use of constitutive models that accurately estimate local states of stress, strain and cyclic plastic strain. However, little research has attempted to systematically consider the sensitivity of overall cyclic stressstrain hysteresis and higher order mean stress relaxation and plastic strain ratcheting responses introduced by the slip system back-stress formulation in crystal plasticity, even for face centered cubic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…The observed differences are postulated to originate from the nature of the materials having different deformation behaviour. The CS steels investigated in the previous report by using the same methodology typically exhibit predominantly bcc phase, while the non‐ferrous alloys examined in this study are reported to have close packed (fcc or hcp) crystal structure; it is well known that the deformation behaviour in these crystal structures are different.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The observed differences are postulated to originate from the nature of the materials having different deformation behaviour. The CS steels investigated in the previous report by using the same methodology typically exhibit predominantly bcc phase, while the non‐ferrous alloys examined in this study are reported to have close packed (fcc or hcp) crystal structure; it is well known that the deformation behaviour in these crystal structures are different.…”
Section: Discussionmentioning
confidence: 76%
“…In the current investigation, the contribution of the fourth backstress component for the non‐ferrous alloys is found to be significantly higher compared with that for ferrous alloys (Tables and Table ). It is postulated here that the deformation behaviour of primarily bcc crystal structures of ferrous alloys and that of the fcc or hcp crystal structures of non‐ferrous materials are resulting in the difference. This assumption is commensurate with the consideration that the combined hardening model used in the present study can phenomenologically capture the micromechanical aspects of material deformation, as discussed by Chaboche …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These researchers simulated the first few cycles and then extrapolated their results to larger cycle numbers. More recently, Hennessey et al (2017) and Cruzado et al (2017) proposed to change the kinematic hardening law from an Frederick and Armstrong (2007) formulation to a modified Ohno and Wang (1993) (Cruzado et al, 2012;Azzouz et al, 2010;Mary and Fouvry, 2007) to extrapolate the constitutive response. Both groups focus on the macroscopic properties of the aggregate rather than on local stress and strain distributions.…”
Section: Introductionmentioning
confidence: 99%
“…For realistic simulations of the cyclic material behavior, the use of appropriate constitutive models is also important in addition to adequate RVEs. Cyclic loading conditions including mean stresses require kinematic hardening (KH) models which are not only able to capture first order stress-strain hysteresis behavior but also higher order phenomena such as mean stress relaxation behavior [17]. It has been widely noted in literature for J 2 plasticity that the Armstrong Frederick KH model failed to predict the mean stress evolution in cyclic loadings with non-zero mean stresses [18,19].…”
Section: Introductionmentioning
confidence: 99%